Visualizing the Sacred: Cross-Cultural Constructions of Fear and Religious Authority in Horror Cinema - Aisyah, Ratu Kasih; Akhmad Siddiq (Faculty of Ushuluddin and Philosophy, 2025)
Horror cinema functions as a powerful medium for articulating cultural anxieties about the metaphysical and the sacred. While Western horror frequently reflects concern about the erosion of religious faith, Southeast Asian horror, particularly in Indonesia, remains deeply embedded in localized theological traditions. This study examines contrasting representations of religious fear by comparing the construction of Demons in Western cinema (The Exorcist, Hereditary) and Jinn in Indonesian cinema (Qodrat, Pengabdi Setan). Drawing on Roland Barthes’s semiotic framework, specifically the interplay of denotation, connotation, and myth, this research decodes key religious signifiers, including the crucifix, exorcism rituals, Qur’anic recitation (ruqyah), and cultic imagery. The findings reveal a marked cosmological divergence: Western horror tends to portray the demonic as a symptom of a modern spiritual crisis and the tension between faith and secular rationality, whereas Indonesian horror situates the Jinn within the dynamics of public piety, Islamic orthodoxy, and syncretism, and critiques religious authority. Beyond their entertainment value, these films function as cultural texts that construct myths about divine power and spiritual vulnerability. This study contributes to scholarship on religion and media by proposing a cross-cultural semiotic model that demonstrates how horror cinema operates as a theological battleground in the modern imagination.